REPRESENTASI POLIGAMI DALAM FILM ATHIRAH ( STUDI ANALISIS SEMIOTIKA JOHN FISKE) - Simanullang, Erik Pandapotan; Yesicha, Chelsy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Athirah movie is a film that lifts the reality of polygamous life, polygamy is an issue that is still a debate in the community. This is quite interesting because polygamy is still something that causes pros and cons in Indonesian society. Different from previous polygamy-themed films, this film is a true story of a wife's struggle as well as the mother of Vice President Indonesia, Jusuf Kalla. In theory, many women have expressed disagreement on polygamous marriages, but in practice women are always in a cornered position, have no choice and are difficult to bid or even have no ability to reject men's desire for polygamy. Starting from this, some Indonesian filmmakers view the interesting polygamy phenomenon to be lifted into a film masterpiece. This study aims to determine the impact of polygamy for wives and children represented in Athirah films viewed from the level of reality, level of representation and ideology level.This study used qualitative methods analyzed by semiotic analysis of John Fiske. Subjects and objects in this study is the observation of the audio and visual display in the scenes of the film Athirah with data collection techniques used are observation, documentation, and literature study.The results of this study show there is a polygamy representation in the Athirah film. The polygamy representation contained in the film is seen from the three levels stated by Jhon Fiske: at the level of reality, the impact of polygamy on the wife and child is seen in aspects of appearance, manner of speech, behavior, gestures, expression and environment. At the representational level, the technical and conventional codes present in the Athirah film depicting the impact of polygamy on wives and children are reflected through aspects of camera, lighting, music and sound. The level of ideology that can be inferred, the depiction of the polygamy values and the polygamous wife's struggle so that the ideology concluded is the ideology of patriarchy and feminism.Keywords: Representation, Film, Polygamy, Semiotics, Impact